Lleupeko tuwün. An exploratory study on proficiency levels in Mapuzungun among mapuche children in the Araucanía region (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This article presents and discusses the preliminary results of an investigation about the linguistic and communicative competence in mapuzungun of children from an area renowned for its high linguistic vitality. The sample consists of 34 Mapuche children between 6 and 10 years of age. Data were collected through the application of a direct measurement instrument (Questionnaire of Language Proficiency in Mapuzungun). The application was carried out individually at the rural school attended by the participants. The overall results show low levels of language proficiency, and performance is better in comprehension than production. Four cases with medium or high level proficiency in mapuzungun, corresponding to older children, were highlighted. The implications of these results in light of the processes of language acquisition and the intergenerational transmission of mapuzungun are discussed.
Keywords: Mapuzungun; proficiency levels; mapuche children; direct assessment; language acquisition